Revisiting presuppositional accounts of homogeneity - Wehbe, Jad (Proceedings of the Amsterdam Colloquium, 2025)
Homogeneity effects with definite plurals have been argued to constitute a phenomena that is distinct from other types of truth-value gaps [Kri15, KS21]. This paper makes the case for a return to early accounts of homogeneity that treat it as a presupposition. I provide empirical support for this view by showing that homogeneity is sensitive to constraints on presupposition accommodation. I argue that connectedness [EC21] mediates the distribution of local accommodation and that the differences between standard presuppositions and homogeneity are due to the fact that only the latter is non-connected (c.f. [Fox18], which argues for an alternative based on plausibility considerations).